PENYELAMATAN ARSIP DARI BENCANA: KEBIJAKAN DAN IMPLEMENTASINYA - Suci Ramadhani Nalole; Ika Nur Azizah (ADISAM PUBLISHER, 2023)
This article aims to find out the handling of archives and implementation of archive rescue policies at archival institutions in Indonesia. The method used is the study of literature obtained from Government Regulations, article’s journals and the internet. The results showed that the realization of the rescue of archives in archival institutions in Indonesia has been referred to the policy of saving archives. But in the process, there are still obstacles that occur in the activities of saving archives